IMPLEMENTASI KEBIJAKAN PENANGANAN PERMUKIMAN KUMUH DALAM MENUNJANG PEMBANGUNAN KAWASAN TELUK TOMINI DI KECAMATAN DUMBO RAYA KOTA GORONTALO - Putri Diah Rahayu; Rusli Isa; Rustam Tohopi (Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine (1) Implementation of Slum Handling Policy (Self-help Housing Stimulant Assistance) in Supporting the Development of the Tomini Bay Area in Dumbo Raya District by using planning, implementation and reporting indicators. (2) Factors Determining the Success of Implementation of Slum Handling Policy (Self-help Housing Stimulant Assistance) in Supporting the Development of the Tomini Bay Area in Dumbo Raya District by using organizational indicators, interpretation, and implementation. This research method uses a qualitative approach with a qualitative descriptive research type, while the data collection techniques used are observation, interviews and documentation. Based on the results of research analyzed in the field that (1) Implementation of Slum Handling Policy (Self-help Housing Stimulant Assistance) in Supporting the Development of the Tomini Bay Area in Dumbo Raya District using planning, implementation and reporting indicators has been carried out properly. However, based on findings in the field, several obstacles were encountered by Recipients of Self-Help Housing Stimulant Assistance (BSPS), namely difficulty finding building materials due to many queues of buyers, also complaining that the building materials ordered were not sufficient for the construction of their houses, so KPB overcame the shortage using his personal money. (2) Factors that determine the success of the implementation of Slum Handling Policy (Self-help Housing Stimulant Assistance) in supporting the development of the Tomini Bay area in Dumbo Raya District using organizational indicators, interpretation and implementation that have been carried out properly.